Postcards from Europe: The Workings of Memory and the Role of Language in Tuvia Ruebner’s Postcard Poems - Bram, Shahar (European journal of jewish studies, 2016)
Tuvia Ruebner’s postcard poems undermine the stereotypical, commercial image that tourist postcards wish to create. The name of the poem and the structure hint at such postcards, but attempt to change their appearance, to broaden the limits of the present, and integrate the past into it. The poet offers a memento that combines presence and absence, what is visual and what is verbal, and an inner and an outer reality. The individual memory is thus woven into a collective memory. These poems offer a sober worldview where Europe turns out to be the source of pain and longing, alongside great joys and pleasures. Ruebner’s postcard poems subvert the normative boundaries and binary divisions, providing the reader with a deeper look at human nature, and at the workings of memory.